Mobile phone use among e-cyclists at red traffic lights: An observation study in a city of China. (3rd October 2021) - Ni, Jie; Qin, Hongmao; Liu, Xuanyi; Zhang, Yanjia; Tong, Zhiyun; Han, Jingwen
Abstract: Objective: The observation study sought to explore the influencing factors associated with mobile phone use when e-cyclists were waiting for red lights at intersections, which provided a theoretical foundation for solving the potential traffic threat and developing management plans for e-cyclists. Methods: Data regarding e-cyclists were collected through camera conducted at the entrance of multiple intersections in Zhenjiang, China in July 2020. The data was reviewed by playing frame by frame. A statistical analysis was performed with the statistical package SPSS software. After conducting univariate logistic analysis on study variables, the multivariate analysis was adopted based on the binary logit regression model. Results: Among the 1166 e-cyclists observed, 15.01% (n = 175) e-cyclists had operated their mobile phones while waiting for red lights. Young e-cyclists, delivery cyclists were more likely to be involved with mobile phone use. Furthermore, mobile phone use was more observed at intersections in suburban areas and with long waiting time. E-cyclists, who was carrying a child, rarely used mobile phone. All intersections during off-peak times showed an increase in mobile phone use. The results also show that neither e-cyclists themselves nor traffic managers are aware of the risks of mobile phone use and the impact on traffic safety while waiting for a red light. Conclusions: The findings of this research revealed the factors influencing mobile phone use of e-cyclists while waiting for a red light, and indicated that education and behavioral intervention need to be strengthened to improve riding safety at intersections. These results will be helpful in developing programs of electric bicycle management.